Investigation of the geometry effect on air-demand ratio in conduits with a sluice gate - Aydin, Alp Bugra; Baylar, Ahmet; Ozkan, Fahri; Tuna, Muhammed Cihat; Ozturk, Mualla (Emerald Group Publishing Ltd, 2023)
Gated conduits involve high-velocity air-water flow. When the studies on the gated conduits are examined, it is determined that the air-demand ratio changed according to the hydraulic and geometric parameters. However, no study has investigated the effect of the cross-sectional geometry of high-head conduits with a sluice gate on the air-demand ratio. In this study, the effect of conduit cross-sectional geometry on the air-demand ratio is examined. Results indicate that conduit cross-sectional geometry is an important effect on the air-demand ratio, especially at 10% and 15% gate opening rates. It is seen that the effect of the conduit geometry on the air-demand ratio decreases at 20%, and greater gate opening rates. Moreover, a formula for the air-demand ratio is presented relating the air-demand ratio to the gate opening rate, Froude number, hydraulic radius, and conduit length was presented for estimating the air-demand ratio.
Keywords: Dams; barrages & reservoirs; Fluid mechanics; Hydraulics & hydrodynamics; Waterways & canals; Water flow